1990
DOI: 10.1128/mcb.10.7.3492-3504.1990
|View full text |Cite
|
Sign up to set email alerts
|

Procyclic Acidic Repetitive Protein (PARP) Genes Located in an Unusually Small α-Amanitin-Resistant Transcription Unit: PARP Promoter Activity Assayed by Transient DNA Transfection of Trypanosoma brucei

Abstract: At least one of the procyclic acidic repetitive protein (PARP or procyclin) loci of Trypanosoma brucei is a small (5- to 6-kilobase) polycistronic transcription unit which is transcribed in an alpha-amanitin-resistant manner. Its single promoter, as mapped by run-on transcription analysis and UV inactivation of transcription, is located immediately upstream of the first alpha-PARP gene. Transcription termination occurs in a region approximately 3 kilobases downstream of the beta-PARP gene. The location of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Bellofatto and Cross (3) were the first to develop a transformation system for a kinetoplastid protozoan, identifying the sequences flanking the miniexon gene of Leptomonas seymouri necessary for CAT expression. Recently the applicability of the CAT assay to the analysis of trypanosome promoter regions has been confirmed by the functional characterization of the T. brucei procyclin gene promoter (7,34). Here, as well as identifying the VSG gene promoter, we have shown that this technique can be used to identify 3' sequences which may be important in RNA processing in trypanosomes.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Bellofatto and Cross (3) were the first to develop a transformation system for a kinetoplastid protozoan, identifying the sequences flanking the miniexon gene of Leptomonas seymouri necessary for CAT expression. Recently the applicability of the CAT assay to the analysis of trypanosome promoter regions has been confirmed by the functional characterization of the T. brucei procyclin gene promoter (7,34). Here, as well as identifying the VSG gene promoter, we have shown that this technique can be used to identify 3' sequences which may be important in RNA processing in trypanosomes.…”
Section: Discussionmentioning
confidence: 78%
“…This region seems to contain all of the sequence elements necessary for initiation of transcription, as it was sufficient for CAT expression. It does not appear to share any extensive homology with known promoters, notably those of the T. brucei ribosomal DNA (41) and procyclin genes (7,28,34), which, like the VSG gene, are transcribed by an RNA polymerase resistant to a-amanitin. The only noteworthy feature within this sequence is the presence of three TAT TAC direct repeats 23 to 61 bp upstream of the putative transcription start site.…”
Section: Discussionmentioning
confidence: 99%